Exploration techniques for locating offshore geothermal resources - Atkins, Darren Thomas, 1982- (2013)
The world’s oceans hold an abundance of geothermal resources, none of which are being utilized today. The majority of these high temperature resources lie along mid-ocean ridges. Since Iceland is uniquely situated on the Mid-Atlantic Ridge (MAR), which runs right through the center of Iceland, it is likely that there are high temperature geothermal resources offshore Iceland. In order to find suitable locations for future offshore geothermal utilization this research investigated what is already known about the ocean floor around Iceland, both near shore and out in the open ocean. All of the oceans around Iceland were considered in this research; however, the main region of focus was along the Reykjanes Ridge. High temperature hydrothermal vent sites around Iceland such as Steinahóll and Grímsey were addressed, as well as other known and inferred vent sites around Iceland. We then describe exploration techniques that can be used for locating hydrothermal vents such as towing a variety of temperature, chemical, and optical sensors from a ship and the use of various underwater vehicles. Then geophysical methods such as resistivity, magnetic, seismic, and gravity surveys for defining reservoir characteristics were looked at. Many of the established geothermal exploration methods used on land may not work in the same way at sea, so new approaches for these methods need to be developed. We looked into various marine geophysical methods used today and determined how and if they can be used and/or modified for offshore geothermal applications. In addition, a magnetic field study was conducted at the geothermal field Eldvörp, on the Reykjanes Peninsula, as a side project for this thesis. It was not possible to fund a research vessel and conduct a magnetic survey along the Reykjanes Ridge, so an on land survey was carried out. The purpose of this field work was to learn how a magnetic survey is done and how to interpret the data. The same principles can then be applied to a marine survey only the instrument would be ...